Drive current of accumulation-mode p-channel SOI-based wrap-gated Fin-FETs - 张严波 杜彦东 熊莹 杨香 韩伟华 杨富华 (Journal of semiconductors, 2011)
Comparisons are performed to study the drive current of accumulation-mode（AM） p-channel wrap-gated Fin-FETs.The drive current of the AM p-channel FET is 15%-26%larger than that of the inversion-mode （IM） p-channel FET with the same wrap-gated fin channel,because of the body current component in the AM FET, which becomes less dominative as the gate overdrive becomes larger.The drive currents of the AM p-channel wrap-gated Fin-FETs are 50%larger than those of the AM p-channel planar FETs,which arises from effective conducting surface broadening and volume accumulation in the AM wrap-gated Fin-FETs.The effective conducting surface broadening is due to wrap-gate-induced multi-surface conduction,while the volume accumulation,namely the majority carrier concentration anywhere in the fin cross section exceeding the fin doping density,is due to the coupling of electric fields from different parts of the wrap gate.Moreover,for AM p-channel wrap-gated Fin-FETs, the current in channel along 110 is larger than that in channel along 100,which arises from the surface mobility difference due to different transport directions and surface orientations.That is more obvious as the gate overdrive becomes larger,when the surface current component plays a more dominative role in the total current.